Suspended accounts align with the Internet Research Agency misinformation campaign to influence the 2016 US election - Matteo Serafino; Zhenkun Zhou; José S. Andrade; Alexandre Bovet; Hernán A. Makse (EPJ Data Science, 2024)
Abstract The ongoing debate surrounding the impact of the Internet Research Agency’s (IRA) social media campaign during the 2016 U.S. presidential election has largely overshadowed the involvement of other actors. Our analysis brings to light a substantial group of suspended Twitter users, outnumbering the IRA user group by a factor of 60, who align with the ideologies of the IRA campaign. Our study demonstrates that this group of suspended Twitter accounts significantly influenced individuals categorized as undecided or weak supporters, potentially with the aim of swaying their opinions, as indicated by Granger causality.